Persistence of Activated and Adaptive-Like NK Cells in HIV+ Individuals despite 2 Years of Suppressive Combination Antiretroviral Therapy - Hearps, Anna C.; Agius, Paul A.; Zhou, Jingling; Brunt, Samantha; Chachage, Mkunde; Angelovich, Thomas A.; Cameron, Paul U.; Giles, Michelle; Price, Patricia; Elliott, Julian; Jaworowski, Anthony (Frontiers in Immunology, 2017)
Innate immune dysfunction persists in HIV+ individuals despite effective combination antiretroviral therapy (cART). We recently demonstrated that an adaptive-like CD56dim NK cell population lacking the signal transducing protein FcRγ is expanded in HIV+ individuals. Here we analysed a cohort of HIV+ men who have sex with men (MSM, n=20) at baseline and following 6, 12 and 24 months of cART, and compared them with uninfected MSM (n=15) to investigate the impact of cART on NK cell dysfunction. Proportions of NK cells expressing markers of early (HLA-DR+/CD38+ and CD69+) and late (HLA-DR+/CD38+) activation ed NK cells were elevated in cART-naïve HIV+ MSM (p=0.004 and 0.015 and 0.004, respectively), as were adaptive FcRγ- NK cells (p=0.003). Using latent growth curve modelling, we show that cART did not reduce levels of adaptive FcRγ- NK cells (p=0.115) or activated HLA-DR+/CD38+ NK cells (p=0.129) but did reduce T cell and monocyte activation (p<0.001 for all). Proportions of adaptive FcRγ- NK cells were not associated with NK cell, T cell or monocyte activation, suggesting different factors drive CD56dim FcRγ- adaptive NK cell expansion and immune activation in HIV+ individuals. Whilst proportions of activated CD69+ NK cells declined significantly on cART (p=0.003), the rate was significantly slower than the decline of T cell and monocyte activation, indicating a reduced potency of cART against NK cell activation. Our findings indicate that two years of suppressive cART have no impact on adaptive CD56dim FcRγ- NK cell expansion and that NK cell activation persists after normalisation of other immune parameters. This may have implications for the development of malignancies and co-morbidities in HIV+ individuals on cART.